What a difference three years of economics education make: Evidence from lower-track schools in Germany - Mira Eberle; Luis Oberrauch (ZBW - Leibniz Information Centre for Economics, 2022)
A large body of literature documents that school-based financial education generally improves financial knowledge, yet little is known about the effect of instruction in the broader economic domain. This paper evaluates the effect of a curriculum reform introducing mandatory economic education on economic competence and knowledge in German lower-track schools, in which students have lower socio-economic status and end up having lower incomes when entering the workforce. While we find small but positive effects on basic economic knowledge and interest in economic matters, we observe no effects on competences, i.e., factual and procedural knowledge in the economic domain. Quantile regressions reveal that the effect on students' knowledge is widely consistent across the entire distribution. With regard to socio-demographic characteristics, we observe strong gender differences already before adulthood.
Keywords: A21; I21; 330; Economic education; economic knowledge; gender gap